Measuring collective behaviour in football teams : inspecting the impact of each half of the match on ball possession - Manuel Clemente, Filipe; Couceiro, Micael; M. L. Martins, Fernando; Mendes, Rui; Figueiredo, António ([Cardiff Metropolitan University], 2013)
The aim of this study was to inspect the influence of each half of matcha and the ball possession status on the players’ spatio-temporal relationships. Three official matches of a professional football team were analysed. From the players' locations were collected the team’s wcentroid, wstretch index, surface area and effective area of play at 9218 play instants. The results suggested that the values of teams’ dispersion and average position on the field decreases during the 2nd half of the match. In sum, this study showed that the half of match and the ball possession status influenced players’ spatio-temporal relationships, in a way that significantly contributes to the collective understanding of football teams.
Keywords: Football; collective behaviour; metrics; match analysis